(untitled) (American Journal of Islam and Society, 2014)
This volume contains an impressive number of essays by authors from diverse backgrounds. What the title does not indicate is the reason for this publication – the conference “Layers of Islamic Art and the Museum Context” (held in Berlin during January 13-16, 2010) in cooperation with the Aga Khan Trust for Culture, the Museum of Islamic Art in Berlin, and the “Europe in the Middle East – The Middle East in Europe” (EUME). The EUME is a Berlin-based research program initiated by the Brandenburg Academy of Science, the Fritz Thyssen Foundation, Wissenschaftskolleg zu Berlin, and the Forum Transregionale Studien. This publication drew upon the expertise of the Aga Khan Network and experts in Germany because it was originally to be a workshop focused on the reorganization of Berlin’s Museum of Islamic Art (MIA) as well as a study for Toronto’s Museum of Islamic Art, which will open this year and house the Aga Khan’s personal collection. The forum offers a certain diversity of voices regarding issues in general (the display of Islamic art around the world) and specific to the MIA at the Pergamon Museum. Its twenty-nine essays are divided into five sections: “In- 132 The American Journal of Islamic Social Sciences 31:2 troduction,” ...